A study of the financial health of the telecom sector - Rajat Kathuria; Mansi Kedia; Richa Sekhani (Indian Council for Research on International Economic Relations (ICRIER), 2019)
India's telecom sector is one of the largest and fastest growing networks across the globe. The increase in subscriptions has been nothing short of dramatic. Increasingly consumers are using phones to decrease transaction costs, access information and become more productive. Data price has fallen, while data consumption per subscriber per month has increased dramatically. While growth has been robust, the financial health of operators has become less rosy especially after the entry of Reliance Jio in the industry. There can be no denying the fact that a strong financial condition of the sector is desirable not only for its own sake, but for the sake of creating a robust platform on which other businesses can participate and thrive. Accordingly, this paper looks at trends across the industry, attempting to take stock of sectoral health through an examination of financial metrics by evaluating profitability and viability on the basis of revenue, cash flows, asset utilization, operating margins, return on equity/ capital employed and degree of leverage for the period 2011-2018. When measured for all operators, the sector appears to have experienced a slowdown in the rate of growth in revenue, especially towards the latter years of our analysis. Addressing regulatory burden and boosting infrastructure investment is important for the industry to remain competitive.
Keywords: L96; H83; 330; Telecom Sector; Financial Analysis